Prognosis of C4 dislocation with spinal cord injury following psychological intervention - Zhao, Min-Chao (J Int Med Res, 2021)
OBJECTIVE: To investigate the effect of psychological intervention on the prognosis of patients with C4 dislocation and spinal cord injury. METHODS: We investigated target patients admitted between 2010 and 2018. Patients’ mental state, quality of life and neurological function at different time points were evaluated to examine the relationship between psychological intervention and recovery and prognosis of acute and critical spinal cord injury. RESULTS: All patients showed improvements in clinical symptoms, neurological function and quality of life. Psychological intervention significantly improved Zung Self-Rating Anxiety Scale score, Zung Self-Rating Depression Scale score and SF-36 Mental Component Summary score within 3 months. Japanese Orthopaedic Association neurological function score and SF-36 Physical Component Summary score were significantly improved after 1-year follow-up. Psychological intervention did not improve 2-year survival. CONCLUSION: Timely and professional psychological intervention can eliminate the psychological disorders of C4 dislocation patients with spinal cord injury. This has a positive effect on their quality of life and prognosis.